Entre o sistema e o mundo da vida: possibilidades de ação comunicativa na trajetória formativa de professores de Ciências - Chapani, Daisi Terezinha; Carvalho, Lizete Maria Orquiza de [UNESP] (My University, 2010)
This study aimed at both identifying possibilities of communicative action that occur in the formative trajectory of Science teachers, and therefore collaborate in the discussion on the rationality approach that supports teacher education. Therefore, we hope to contribute for the construction of a formative model that encourages human emancipation. For this purpose, we draw concepts from Communicative Action Theory proposed by Jürgen Habermas. Data were obtained by half-structuralized interviews. Although strategic actions predominate among those used by teachers during their education period, we observed some tension focus could be identified, better recognized and built up in order to enlarge possibilities of increasing communicative actions in teacher education. We identified political and epistemological factors as obstacles for these possibilities to materialize.

Este estudo teve por intenção identificar possibilidades de ação comunicativa na trajetória formativa de professores de Ciências e, dessa forma, colaborar com a discussão dos tipos de racionalidade que fundamentam essa formação. Espera contribuir para a elaboração de um modelo formativo que favoreça a emancipação do ser humano. Para tanto, utiliza conceitos provenientes da Teoria da Ação Comunicativa proposta por Jürgen Habermas. Os dados foram constituídos por meio de entrevistas semi-estruturadas. Embora as ações estratégicas predominem entre aquelas usadas pelos docentes em sua formação, ocorreram focos de tensão que podem ser identificados, tematizados e ampliados, de maneira que se alarguem as possibilidades de ações comunicativas na formação docente. Foram identificados fatores políticos e epistemológicos como impedimentos para que essas possibilidades se concretizem.
Between systems and world life: possibilities of communicative actions on science teachers’s trajetory
Keywords: Teachers education; Communicative action; Communicative action; Theory proposed by Habermas; Formação docente; Ação comunicativa; Teoria da ação; Comunicativa de Habermas